Romiplostim – an emergency treatment of intracranial haemorrhage in the course of severe primary immune thrombocytopaenia - Łaguna, Paweł; Sikorska, Aleksandra; Kulik, Joanna; Matysiak, Michał (Pediatria Polska - Polish Journal of Paediatrics, 2022)
We present a case of a 16-year-old girl with newly diagnosed/persistent immune thrombocytopaenia (ITP) with a complication of intracranial haemorrhage. She did not respond adequately to first-line treatment, i.e. intravenous immunoglobulin infusions, glucocorticosteroids, and transfusion of platelets, and developed numerous bleeding complications. During the treatment she developed bleeding into the central nervous system, which is a rare and devastating complication of ITP. In such cases, the available data in the literature suggest a potential role of the thrombopoietin receptor agonist as a life-saving emergency treatment for severe, newly diagnosed immune thrombocytopaenia. The prognosis of our patient’s survival and neurological status was completely dependent on this treatment. After obtaining consent from the appropriate bioethics committee, romiplostim was administered to the patient, with a good response and without side effects.